New Mediums, Better Messages? How Innovations in Translation, Engagement, and Advocacy are Changing International Development - Lewis, David; Rodgers, Dennis; Woolcock, Michael (Oxford University Press, 2022)
The notion of development influences and is influenced by all aspects of human life. Social science is but one representational option among many for conveying the myriad ways in which development is conceived, encountered, experienced, justified, courted, and/or resisted by different groups at particular times and places. As international development has become more quantitative and economics-centred, there is an enduring sense that what is measured (and thus 'valued' and prioritized) may have become too narrow, that the powers of prediction claimed by some areas of economics and management may have overreached, and that the human dimension is in danger of being lost. Reflecting this concern, New Mediums, Better Messages? contributes to new conversations between science, social science, and the humanities around the roles of different kinds of knowledge, stories, and data play in relation to global development. It brings together a team of multidisciplinary contributors to explore popular representions of development, including music, blogs, and fiction.